Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fürst, J. U.; Strekalov, D. V.; Elser, D.; Aiello, A.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Whispering gallery mode (WGM) resonators feature strong optical confinement, small mode volume, and offer tunable coupling to an external optical field. Fabricating WGM resonators from lithium niobate one can take advantage of these properties to achieve very strong optical nonlinear response, e. g. parametric downconversion (PDC). This process offers a highly wavelength tunable light source and is used as a state of the art source for nonclassical light. Driving PDC in cavities, also referred to as an optical parametric oscillator (OPO), provides efficient wavelength conversion. Thus, it is intruiging to investigate PDC in a WGM resonator, although phase matching conditions become involved in spherical geometry. In the process of higher harmonic generation, quasi phase-matching has already been demonstrated in a lithium niobate WGM cavity [1, 2], showing the potential of these resonators. Here we present a highly efficient OPO with a WGM resonator using natural temperature phase matching, where the individual optical fields have narrow optical linewidth [3]. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05